KINERJA GURU DALAM PEMBELAJARAN - Merthi Satya Perdana; Rohiat Rohiat (UNIVERSITAS BENGKULU, 2020)
This research described geographic Teacher’s perpormance at SMA Negeri 1 Kepahiang. This Research used descriptive qualitative method. Which emprasize on the real description and the truth of teacher’s perpormance in learning geography at SMA Negeri 1 Kepahiang. The main subject of this Research is geography Teacher’s. The result of this research indicate that teacher’s perpormance in learning geography had covered; 1) The design of learning geography had conduct by the 10th grade socrety teacher’s with arrage the syllabus and learning implementation draft contarned: Subject indentity, Standard competence, Basic competence, Indicator of achievement competence learning pupose, lesson materrals, Time allocation learning method, Study resources, The study result assessment. 2) The geography learning implementation held from introduction, contetnt, and closing activities. 3)The geography learning evaluation had done by teacher appropriate with assessment orientation, and the development of result study with remedial and enrichment activities. Based on the result of this research it could be concluded that teacher perpormancein learning geography societyprogram wich heid by the geography teacher’s in 10th grade at SMA Negeri 1 Kepahiang.